O silêncio administrativo e a efetividade do licenciamento ambiental no âmbito do município de Tibau do Sul - Rio Grande do Norte, Brasil - Silva, Priscila Freire da (2023)
This research examines the effectiveness of socio-environmental licensing, a central instrument of the National Environmental Policy (Art. 9, IV), in the context of administrative silence in Tibau do Sul, RN. The study focuses on the legal consequences of this silence, evidenced in the actions of the State Public Ministry (MPE-RN) and the Federal Public Ministry (MPF-RN) between 2016 and 2020. Three main questions guide the investigation: How do the MPF-RN and MPE-RN observe the administrative silence in their extrajudicial procedures and legal proceedings that deal with environmental licensing of tourist developments in Tibau do Sul, during the period from 2016 to 2020? (2) What are the socio-environmental normative developments that make this identification possible? (3) What are the implications for the effectiveness of environmental licensing of tourist developments in Tibau do Sul, through the identification of cases of administrative silence in the procedures and legal processes of MPE-RN and MPF-RN? The methodology adopted is interdisciplinary, combining theoretical, normative and jurisprudential analysis to address these issues. The dissertation is structured into three main chapters: the first, of a more theoretical and comprehensive nature, addresses the Environmental Rule of Law, sustainability and public policies, interconnecting environmental licensing and administrative silence. There is an institutional and regulatory crisis that affects the environmental management intended by licensing. The second chapter investigates how the MPF-RN addresses administrative silence, identifying the relevant normative developments. Finally, the third chapter evaluates the implications of this silence on the effectiveness of environmental licensing in Tibau do Sul. In the final considerations, based on a cross-reflection of the three chapters, guidelines are suggested for more effective state and social action in environmental protection. It is recommended that both the government and civil society intensify monitoring and inspection of environmental licensing, with the support of institutions such as the MPF, to guarantee the defense of collective rights and environmental sustainability.